Use of Voltammetry for Determining Antibiotics Streptomycin and Azitromycin; Journal of Analytical Chemistry; Vol. 60, iss. 6 - Fedorchuk V. A.; Puchkovskaya E. S. Evgeniya Sergeevna; Anisimova L. S.; Slepchenko G. B. Galina Borisovna (2005, 2005)
Title screen